Hierarchy of clinical decision-making by physicians based on medical and ethical decision making - Soffan, Mochammad; Trisnadi, Setyo (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2022)
From 2011 to 2014, there were six cases of suspected medical malpractice in the Central Java Region; four clinical cases were resolved by an ethics board and two by a public court, so that it serves as a reference for clinical decision-making for physicians, as many ethical problems in addition to legal problems exist in medicine. Doctors, as Indonesian citizens, are obligated to implement the norms and laws that apply in Indonesia. However, as professionals, they are also obligated to implement the norms that apply in medical professional organisations (Indonesian Doctors Association/IDI), including the Indonesian Doctors Association (IDI), the Code of Medical Ethics (KODEKI), and interprofessional ethics. So that the actions of physicians can be accounted for from both a legal and an ethical standpoint of the medical profession. Every clinical case a physician encounters has inextricable ethical and medical dimensions, necessitating a prudent method for making clinical decisions. The challenge is to comprehend the value hierarchy, beginning with norms, morals, principles, standards, and rules. Therefore, when making clinical decisions, physicians are truly guided by the order of applicable values, one of which is Jonsen-4-box Siegler’s method. The culture of the Indonesian people includes a 4-box method as an alternative. Schematics can be made for the order of values and ways of making clinical decisions based on wise ethical decisions in resolving ethical dilemmas and medical disputes.